Novel highly dispersible, thermally stable core/shell proppants for geothermal applications. (November 2017) - Childers, Ian M.; Endres, Mackenzie; Burns, Carolyne; Garcia, Benjamin J.; Liu, Jian; Wietsma, Thomas W.; Bonneville, Alain; Moore, Joseph; Leavy, Ian I.; Zhong, Lirong; Schaef, Herbert T.; Fu, Li; et al.
Graphical abstract: Highlights: CO2 -responsive core/shell proppant. Lightweight, does not require highly viscous fluids to disperse the proppant. CO2 triggers proppant aggregation and emplacement via crosslinking of polymer shell. High thermal and chemical stability in geothermal brines. Potentially applicable in geothermal as well as in unconventional oil and gas recovery. Abstract: The use of proppants, especially larger and more dense proppants, during reservoir stimulation in tight oil and gas plays requires the introduction of highly viscous fluids to transport the proppants (mm–mm) with the fracturing fluid. The highly viscous fluids required result in increased pump loads and energy costs. Furthermore, although proppant deployment with fracturing fluids is a standard practice for unconventional oil and gas stimulation operations, there are only a few examples in the US of the applying proppant technology to geothermal energy production. This is due to proppant dissolution, proppant flowback, and loss of permeability that, although also occurs during unconventional oil/gas stimulation (hydraulic fracturing) operations, it is amplified under the extreme temperatures found in enhanced geothermal systems (EGS). This work demonstrates proof-of-concept of a novel, CO2 -responsive, lightweight sintered-bauxite/polymer core/shell proppant. The polymer shell has two main roles; (1) increase the stability of the proppant dispersion in water without the addition of rheology modifiers, and (2) once at the fracture network react with CO2 to promote particle aggregation and prop fractures open. In this work, both roles are demonstrated together with the thermal and chemical stability of the materials showing the potential of these CO2 -responsive proppants as an alternative proppant technology for geothermal and unconventional oil/gas applications.